EXPRESSION OF SUBJECTIVE ATTITUDE IN VERBS IN UZBEK LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article explores expression of subjective attitude in verbs in Uzbek language. It is known that attitude means a person's view of reality, the things in it - events, the principle of approach, and it is a logical concept that expresses the nature of the location of elements in a certain system and the interdependence of their connections. So, the words evaluation and attitude are closely related to each other, and in Uzbek linguistics, the terms "evaluative attitude", "subjective attitude", "positive attitude", "negative attitude" are widely used by linguists. Both action verbs and state verbs can be used to express the meaning of attitude . But the verbs used in relation function also have their own stylistic features. The meanings of attitude verbs are also clarified in context. The author tried to analyze “neutral attitude”, “evaluation attitude", "subjective attitude", "positive attitude", "negative attitude" and modal attitude" in Uzbek language.